Modeling a Viscoelastic Gymnastics Landing Mat During Impact - Mills, C.; Pain, M. T. G.; Yeadon, M. R. (Journal of Applied Biomechanics, 2006)
Landing mats that can undergo a large amount of area deformation are now essential for the safe completion of landings in gymnastics. The objective of this study was to develop an analytical model of a landing mat that reproduces the key characteristics of the mat-ground force during impact with minimal simulation run time. A force plate and two high-speed video cameras were used to record the mat deformation during vertical drop testing of a 24-kg impactor. Four increasingly complex point mass spring-damper models, from a single mass spring-damper system, Model 1, to a 3-layer mass spring-damper system, Model 4, were constructed using Matlab to model the mat`s behavior during impact. A fifth model composed of a 3-layer mass spring-damper system was developed using visual Nastran 4D. The results showed that Models 4 and 5 were able to match the loading phase of the impact with simulation times of less than 1 second for Model 4 and 28 seconds for Model 5. Both Models 4 and 5 successfully reproduced the key force-time characteristics of the mat-ground interface, such as peak forces, time of peak forces, interpeak minima and initial rates of loading, and could be incorporated into a gymnast-mat model.